2013
DOI: 10.1097/pec.0b013e31827b2299
|View full text |Cite
|
Sign up to set email alerts
|

The Wong-Baker Pain FACES Scale Measures Pain, Not Fear

Abstract: The WBS demonstrates moderate correlation with another measure of pain (VAS) and is not mistaken for fear among school-aged patients presenting to the ED with pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 10 publications
1
84
0
2
Order By: Relevance
“…This study used a combination between two common validated rating scales, an NRS and the Wong-Baker FPS, for a correct pain assessment in children. 21 This is in agreement with work published by Needleman et al, 5 which used a combination of the FPS and the Color Analog Scale, and that of Haliciog lu et al, 18 who used an NRS. Agreement between the FPS and the standard visual analog scale used by Gecgelen et al 19 was previously documented.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This study used a combination between two common validated rating scales, an NRS and the Wong-Baker FPS, for a correct pain assessment in children. 21 This is in agreement with work published by Needleman et al, 5 which used a combination of the FPS and the Color Analog Scale, and that of Haliciog lu et al, 18 who used an NRS. Agreement between the FPS and the standard visual analog scale used by Gecgelen et al 19 was previously documented.…”
Section: Discussionsupporting
confidence: 82%
“…The measurement of pain in children can be even more difficult and has been a frequent subject of discussion. 21,23 Studies have shown that children 3 years and older are capable of understanding the concept of hurt and its varying degrees of intensity, if provided with an appropriate device. This study used a combination between two common validated rating scales, an NRS and the Wong-Baker FPS, for a correct pain assessment in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 An observational study reported that the WBS showed a moderate correlation with other pain scales in school-aged patients. 28 We did not perform plasma selenium measurements. A study by Dwipoerwantoro assessed the effect of selenium deficiency on the enzymatic antioxidant defense system (superoxide dismutase/ SOD, chatalase/CAT, gluthathione peroxidase/GPX) and non-enzymatic molecules (gluthathione/GSH, thiobarbituric acid reactive substances/TBARS, and thiols) in the liver and muscle tissue of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic efficacy was obtained from each volunteer using visual analogue scale (VAS) and numerical rating scale (NRS) as described by FerreiraValente and coworkers (27) as well as Wong-Baker faces pain rating scale (WPS) (28). Briefly, the VAS is a 100 mm horizontal line; left end (0 mm) represents no pain and right end (100 mm) represents the most imaginable pain.…”
Section: Efficacy Of Lh-rng and Ph-rng On Pain Reductionmentioning
confidence: 99%